KUALITAS PELAYAN PUBLIK PADA KANTOR KELURAHAN GILINGAN KECAMATAN BANJARSARI KOTA SURAKARTA - Joko Suranto, Siti Ngaisah & (JI@P, 2017)
Siti Ngaisah, 2016 âThe Quality Of Public Service At The Mill Office OfGilingan Banjarsari Of Surakarta Urban Governmentâ. Slamet RiyadiUniversity, Thesis, unpublished.Goals to be achieved by this study are to describe the quality of public serviceat the Mill Office Gilingan Banjarsari of Surakarta. The method used in thisresearch is descriptive and analyzed qualitative. Its informant is Gilinganemployee Banjarsari of Surakarta. Data was collected through interviews,observation, and documentation. Data analyzed using an interactive model,namely data collection, data reduction, data presentation, and conclusion.Mechanical validity of the data using triangulation. Based on the results ofresearch and discussion can be concluded that the quality of public services atthe mill office is described as follows: 1) The quality of public services at themill office is based on indicators Tangibles (direct evidence) basically beenimplemented, parking facilities are less qualified because of the narrownessland can still be overcome. To provide service tangibles (direct evidence) thatneed to be improved and its quality; 2) The quality of public services indicatorsReliability (reliability) has been implemented fairly well, there is little constraintof service does not match the time is still within reasonable limits due to thenumber of employees that are not proportional to the number of people; 3)Quality indicators Responsiveness of public service (responsiveness), hasbeen carried out by well-Gilingan mill officer. Responsiveness service quality(responsiveness) need to be improved quality; 4) Quality Assurance indicatorof public services (guarantee), has been implemented by well-trainedemployees with the mill 0ffice to provide security and correctness. QualityAssurance services (guarantee) for improvement of quality; 5) The quality ofpublic services Emphaty indicator (empathy) are good enough carried out byemployees of the mill office so there are social interaction between employeesof the office and community service users. The results of this research showedthat the public service in the mill office is already running well despite notmaximized due to several constraints for their facilities and infrastructure areinadequate, constraint techniques and human resources, but everything canstill be resolved so that public services can be run as planned.Key words: tangible, reliability, responsiveness, Assurance, dan Emphaty.